2024
DOI: 10.1152/ajpheart.00462.2023
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac reverse remodeling in a mouse model with many phenotypical features of heart failure with preserved ejection fraction: effects of modifying lifestyle

Mohamed Lamine Aidara,
Élisabeth Walsh-Wilkinson,
Sara-Ève Thibodeau
et al.

Abstract: Multiple factors cause heart failure with preserved ejection fraction (HFpEF) and involve various systems. HFpEF prevalence is rapidly rising, and its prognosis remains poor after the first hospitalization. Adopting a more active lifestyle has been shown to provide beneficial clinical outcomes for HFpEF patients. Using a two-hit HFpEF murine model, we studied cardiac reverse remodelling (RR) after stopping the causing stress and introducing voluntary exercise (VE). We checked in 2-month-old male and female C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
7
1
Order By: Relevance
“…It was unsuspected that AngII infusion in old Ovx mice would tend to normalize the expression of clock genes towards levels measured in young females instead of the opposite. We recently observed in young female mice treated with combined AngII and a high-fat diet that expression of Arntl, Ciart, and Per2 was all modulated in the opposite direction we observed here ( Aidara et al, 2024 ). The current knowledge of the control of cardiac clock genes does not provide much to explain this observation, and further studies are needed to both confirm and understand it better.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…It was unsuspected that AngII infusion in old Ovx mice would tend to normalize the expression of clock genes towards levels measured in young females instead of the opposite. We recently observed in young female mice treated with combined AngII and a high-fat diet that expression of Arntl, Ciart, and Per2 was all modulated in the opposite direction we observed here ( Aidara et al, 2024 ). The current knowledge of the control of cardiac clock genes does not provide much to explain this observation, and further studies are needed to both confirm and understand it better.…”
Section: Discussioncontrasting
confidence: 60%
“…Sham surgery was performed without the placement of a vehicle-filled osmotic minipump in all animals. Previous studies have shown that this had not caused differences in the heart ( Matsiukevich et al, 2023 ; Aidara et al, 2024 ).…”
Section: Study Limitationsmentioning
confidence: 82%
See 3 more Smart Citations